The Role of Big Data Technology in HRM Decision Making - Budi Rismayadi (SEAN Institute, 2024)
This research aims to explore and analyze the role of Big Data technology in the context of Human Resource Management (HRM) decision making. The development of information technology, especially Big Data, has enabled organizations to collect, store and analyze large and varied volumes of data quickly. In the context of HRM, Big Data technology promises great potential in improving the quality of decision making related to employee management, recruitment, employee development, performance evaluation and talent management. The research method used is a qualitative approach with descriptive methods. The research results show that the application of Big Data technology in Human Resource Management (HRM) decision making provides great potential for increasing the effectiveness and efficiency of the workforce management process. By analyzing employee data from various sources, organizations can identify trends, patterns and opportunities that are undetectable through conventional methods, and predict future workforce needs. However, challenges such as data privacy, the complexity of data integration, and the need for strong analytical skills, must be overcome so that the application of Big Data in HRM can provide maximum benefits for companies. With a holistic and integrated approach, organizations can harness the potential of Big Data to improve HR strategies, improve employee performance, and achieve larger business goals.